Syntheses, crystal structures, and Jack bean urease inhibitory activities of copper(II) complexes derived from 4-tert-butyl-N′-(1-(pyridin-2-yl)ethylidene)benzohydrazide. Issue 20 (18th October 2017) - Guo, Sihan; Wang, Tianrui; Xin, Jiajin; Hu, Qiqige; Ren, Shanfa; Sheng, Guihua; Pan, Lin; Zhang, Chenglu; Li, Kun; You, Zhonglu
Abstract: Two new copper(II) complexes, [CuL(HL)]·ClO4 (1 ) and [Cu2 Br2 L2 ]·0.85H2 O (2 ), where L is the monoanionic form of 4- tert -butyl- N′ -(1-(pyridin-2-yl)ethylidene)benzohydrazide (HL), have been prepared. The complexes were characterized by infrared and UV–vis spectra, and single crystal X-ray diffraction. Complex1 is a mononuclear copper(II) species and2 is a bromido-bridged dinuclear copper(II) species. The Cu ion in1 is in an octahedral coordination mode and that in2 is trigonal-bipyramidal. The Jack bean urease inhibitory assay indicated that2 is active, with IC50 value of 20.6 ± 2.3 μmol L −1, while1 is inactive. Molecular docking of2 with Jack bean urease was studied. Abstract :